A supramolecular self-assembly material based on a quinoline derivative and its sensitive response toward volatile acid and organic amine vapors. (28th March 2018) - Cao, Xinhua; Ding, Qianqian; Gao, Aiping; Li, Yiran; Chang, Xueping; Wu, Yongquan
Abstract : A new gelator1, containing a quinoline group, was designed, synthesized, and fully characterized. Abstract : A new gelator1, containing a quinoline group, was designed, synthesized, and fully characterized. It was found that a stable organogel of1 could be obtained in some solvents, including ethanol, acetonitrile, n -hexane, petroleum ether, and DMSO. It is worth mentioning that a supragel was formed in hexane and petroleum ether with critical gel concentrations of 0.16% and 0.17%, respectively. The self-assembly process of gelator1 in the above five solvents was carefully investigated by FESEM, UV-vis, FL, FTIR, XRD, and water contact angle experiments. It was found that gelator molecule1 could self-assemble into different self-assembly structures with different surface wettabilities – from super-hydrophilicity to super-hydrophobicity – in the self-assembly process. The organogel of1 that was formed in acetonitrile could emit strong light when compared with that emitted by organogel1 in the other four solvents under the stimulation of 365 nm light. At the same time, the fluorescence emission of the organogel state had a red-shift of 70 nm when compared with that of the solution state. The fluorescence emission of molecule1 in solution and its gel state was further and well verified via theoretical calculations. The fluorescence emission of the acetonitrile solution of gelator1 could reversibly respond to TFA and TEA, along with a change in the maximum emission wavelength between 382 nm and 458 nm, in turn. The xerogel of1 formed in acetonitrile exhibited a sensitive responsive ability towards TFA and TEA. More interesting are the different changes in behavior of the fluorescence emission of molecule1 in solution and the xerogel state in response to TFA and TEA. This research will provide a new way to design multi-functional soft matter materials that show a response to volatile acid and organic amine vapors.